2016
DOI: 10.1097/sle.0000000000000259
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Adhesiolysis for Small Bowel Obstruction: A Single-Center Retrospective Case-Control Study

Abstract: The laparoscopic approach for SBO is feasible because of its fewer complications and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Turning to the length of hospital stay, in agreement with several studies,[ 8 , 9 , 21 ] laparoscopic adhesiolysis is associated with a dramatic decrease in hospital stay in comparison to open adhesiolysis. Lin et al .…”
Section: Discussionsupporting
confidence: 86%
“…Turning to the length of hospital stay, in agreement with several studies,[ 8 , 9 , 21 ] laparoscopic adhesiolysis is associated with a dramatic decrease in hospital stay in comparison to open adhesiolysis. Lin et al .…”
Section: Discussionsupporting
confidence: 86%
“…The studies span an 11‐year period from 2010 to 2021. The studies included 54 retrospective cohort studies [17–70], eight prospective cohort studies [4, 71–77], seven RCTs [78–84], and four retrospective case–control studies [85–88]. 45 studies were single centre, 20 utilised databases and 8 were multicentre.…”
Section: Resultsmentioning
confidence: 99%
“…In the series presented by Halabi et al, the average length of stay for all patients undergoing surgery for gallstone ileus was 12 days; this is longer than the reported laparoscopic and open postoperative stays noted with adhesive bowel obstructions as measured by Lin et al of 6.4 ± 2.1 and 7.2 ± 2.9, respectively [ 1 , 8 ]. A review of laparoscopic and open cases for gallstone ileus by Moberg and Montgomery showed a shorter, but not statistically significant, length of stay with laparoscopic procedures, 7 days for laparoscopic versus 10 days for open [ 8 , 9 ]. When cholecystectomy, fistula closure, and/or bowel resection are undertaken in addition to the enterolithotomy, the operative time and postoperative length of stay for patients were significantly longer [ 2 ].…”
Section: Discussionmentioning
confidence: 97%